2021
DOI: 10.36253/ahsc-8376
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity assessment of ancient mulberry (Morus spp.) in Lebanon using morphological, chemical and molecular markers (SSR and ISSR)

Abstract: Lebanon has ancient mulberry trees which are the remnants of the abundant orchards that dominated its lands during the nineteenth century. Lebanese mulberry germplasm has not been assessed yet. This study aims to collect local old rainfed mulberry accessions from different geographical regions and assess their diversity by using morphological and molecular markers (SSR and ISSR). Genetic diversity of 70 accessions of mulberry were evaluated by using 27 morphological traits. The dendrogram based on the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…On the contrary, Kadri et al (2021) found a high level of genetic diversity within 70 genotypes of different mulberry species from different geographical regions in Lebanon using the combination of morphological and molecular markers (SSR and ISSR).…”
Section: Genetic Distance and Genetic Diversity Between And Within Mo...mentioning
confidence: 93%
See 1 more Smart Citation
“…On the contrary, Kadri et al (2021) found a high level of genetic diversity within 70 genotypes of different mulberry species from different geographical regions in Lebanon using the combination of morphological and molecular markers (SSR and ISSR).…”
Section: Genetic Distance and Genetic Diversity Between And Within Mo...mentioning
confidence: 93%
“…The molecular characterization and analysis of Morus alba L. cultivars from Cuba, Costa Rica, Brazil, South Korea, Ethiopia, China, Japan, Italy and Spain with SSR markers revealed a genetic distance of 0.570 among the genotypes tested (Garcia-gómez et al, 2019). ISSR and SSR markers have been applied to study mulberry variation and relationships amongst cultivated and wild genotypes (Zhao et al, 2007), and also the use of the same markers showed a high level of genetic diversity within mulberry trees in Lebanon (Kadri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The small, multiple sweet infructescences (soroses) are a consolidation of drupelets with remnants of perianth [10]. The colour of the soroses is not a reliable distinguishing feature for identifying between black and Foods 2023, 12, 3985 2 of 22 white mulberry species, as the latter shows colours ranging from yellowish white to pink, dark red, and black, with different shading as they ripen [11]. The main components of mulberry soroses are primary metabolites, e.g., sugars, organic acids, and proteins, which reach values of 1.44 g/100 g [12][13][14], that are higher than in most berry fruits [15,16].…”
Section: Introductionmentioning
confidence: 99%